Cybersecurity Protocols for Telehealth: Developing new cybersecurity protocols to protect patient data during telehealth sessions - Vivek Yadav (North American Journal of Engineering Research, 2024)
The introduction of telehealth services into the healthcare system sped innovation and transformed the patient's only option to obtain quality care, providing exceptional access and convenience. Nevertheless, while the secure transfer of patient records goes through digital networks, cybersecurity becomes a must for healthcare organizations. This paper deals with the formulation of resilient cyber security protocols particularly applicable to telemedicine environments. Drawing upon a comprehensive review of existing literature, four essential responsibilities are identified: data transmission through encryption, development of access control tools, authorization, as well as observation of the system. These functions assume the role of an ideological compass for pressuring telehealth meetings' privacy and safety. The institutions of healthcare must implement stricter cybersecurity measures so that a malicious data breach will not happen and guarantee that there is patient confidentiality. One of the most essential desires of such policies is to protect patient data, however, what’s more, important is the implication it has on building patients’ trust and widespread adoption of telehealth services. This paper illustrates the significant need for cybersecurity to be the primarycomponent of telehealth practices and sets the scene for further study in this field which is developing at a remarkable pace